L’Espagne et la bataille de l’opinion internationale. Agences de presse, tourisme et réseaux de propagande sous la dictature du général Primo de Rivera : le cas de l’Agence Plus Ultra - David Marcilhacy (Cahiers de Civilisation Espagnole Contemporaine)
During the 1920s, Spain engaged in an authentic battle of international opinion aimed at serving its national interests, increasing its prestige and combating opposing propaganda propagated from abroad. In this respect, the dictatorship of General Miguel Primo de Rivera marked an unprecedented rise in the control of the media and political communication. Based on a study of the archives of the Spanish and French Ministries of Foreign Affairs, this paper will reflect on the propaganda networks developed abroad, in three directions: the strategies of influence deployed towards the foreign media, particularly through the role of embassies; the control of information flows through a national press agency created for this purpose –the Agence Plus Ultra; and the gradual diversification of propaganda vectors, particularly through the promotion of tourism. This will lead us to question both the instruments and the actors of propaganda, to analyse the interconnection between internal and external propaganda and to see to what extent the perspective of networks (informative and touristic) sheds light on the strategies deployed in this field by the Spanish public authorities during the 1920s.